The Effects of Enamel Protective Agents on Shear Bond Strength After Rebonding of Stainless Steel Orthodontic Bracket (An in Vitro Study) - Ruaa Ali K. Al-Sarkhi; Dheaa H. Al-Groosh (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: Bracket rebonding is a common problem in orthodontics which may result in many drawbacks. The aims of this study were to evaluate the effects of application of two enamel protective agents "Icon" and "ProSeal" on shear bond strength before and after rebonding of stainless steel orthodontic brackets using conventional orthodontic adhesive and to assess the site of bond failure. Materials and methods: Fifty sound extracted human upper first premolar teeth were selected and randomly divided into two equal groups; the first time bonding and the rebonding groups (n=30). Each group was subdivided into control, Icon and ProSeal subgroups. The enamel protective agents were applied after etching (preconditioners). Shear bond strength before and after rebonding of stainless steel brackets were assessed using the Universal testing machine and the adhesive remnant index was used to find out the bond failure site using a stereomicroscope. Then the results were statistically analyzed using one-way ANOVA analysis test and T-test. Results: There were no significant differences in the shear bond strength mean values in either group or their corresponding subgroups. Forty percentage of the bond failure in ProSeal groups occurred away from the enamel where 75% of those were at the enamel protective agents/adhesive interface. Conclusions: The application of Icon and ProSeal did not compromise the shear bond strength and the application of the ProSeal may protect the enamel surface from trauma (cracks, chipping or detachment).